PHYSICAL QUALITIES OF CROSSBRED LANDRACE PORK GIVEN BROILER FARM WASTE PROTEIN CONCENTRATE - I M. J., Hermawan; Ariana, I N.T.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2024)
This study aimed to determine the physical quality of crossbred landrace pork given broiler farm waste protein concentrate in the finisher phase pig ration. The pigs used were crossbred Landrace pigs in the finisher phase. The design used was a Complete Random Design with 3 treatments and 4 repeats so that 12 finisher phase pigs were needed with an average body weight of 63.42±2.39 kg. The treatment consisted of rations without KP-LB (0% KP-LB)/control (A), rations with 12% KP-LB (B), and rations with 24% KP-LB (C). The variables observed were pH value, meat color, cooking loss, weep loss, and water holding capacity. The results showed that the physical quality of crossbred landrace pork given broiler waste protein concentrate (KP-LB) was significantly different (P<0.05) against yellowish color (b*) but not significantly different (P>0.05) from pH value, cooking loss, weep loss, water holding capacity, brightness color (L*) and reddish color (a*). Based on the results of the study, it can be concluded that broiler farm waste protein concentrate feed (KP-LB) obtained the physical quality of crossbred landrace pork that can maintain the pH value, cooking loss, weep loss, water holding cpacity, brightness color value (L*) and reddish color value (a*) and can increase the yellowish color value (b*).